Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevc.85.031301
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new isomeric state in68Ni: Evidence for a highly deformed proton intruder state

Abstract: We report on the observation of a new isomeric state in 68 Ni. We suggest that the newly observed state at 168(1) keV above the first 2 + state is a π (2p-2h) 0 + state across the major Z = 28 shell gap. Comparison with theoretical calculations indicates a pure proton intruder configuration and the deduced low-lying structure of this key nucleus suggests a possible shape coexistence scenario involving a highly deformed state. The atomic nucleus is a complex quantum system consisting of two kinds of strongly in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
(42 reference statements)
3
24
0
Order By: Relevance
“…A super cycle (SC) contains up to 40 proton pulses (PP) with a certain sequence, distributed with a difference of 1.2 s between each of them. In the present case, the super cycle consisted of 33 proton pulses of which ISOLDE received 11, non-consecutive ones with numbers: 4,6,8,10,13,18,21,23,26,28, and 31. After each PP a delay time of 10 ms was introduced before the separator beam gate of 5 ms was opened, to let the beam implant on the tape.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…A super cycle (SC) contains up to 40 proton pulses (PP) with a certain sequence, distributed with a difference of 1.2 s between each of them. In the present case, the super cycle consisted of 33 proton pulses of which ISOLDE received 11, non-consecutive ones with numbers: 4,6,8,10,13,18,21,23,26,28, and 31. After each PP a delay time of 10 ms was introduced before the separator beam gate of 5 ms was opened, to let the beam implant on the tape.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Especially the harmonic oscillator shell closure for neutrons at N = 40, separating the negative-parity pf and positive-parity g 9/2 orbitals, makes 68 Ni and adjacent nuclei objects of intensive studies, both experimentally [4][5][6] and theoretically [7,8]. It has been suggested that neutron excitations across the N = 40 sub-shell closure, when moving to lighter Z-values below 68 Ni increases, resulting in the development of collective behavior as protons are removed from the f 7/2 single-particle orbital [9], making this region of the nuclear chart suitable for studying the effects of proton-neutron interactions and the onset of deformation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of both proton and neutron intruder levels sparked a renewed interest in identifying corresponding states in the even-even 68 Ni nucleus and theoretical predications were put forward for the excitation energy of the proton 2-particle 2-hole 0 + state in 68 Ni [18]. Despite initial indications [19] the state has not yet been identified [20].…”
Section: The View Ofmentioning
confidence: 99%
“…Large-scale Shell Model calculations using the Lenzi-Nowacki-Poves-Sieja (LNPS) interaction [3,[5][6][7] Thanks to the great effort put into studying this particular nucleus over the recent decades shape coexistence in 68 Ni is well established both from an experimental [3,[9][10][11][12] and a theoretical point of view [3,5,8]. But the situation is not that clear for nuclei around it.…”
mentioning
confidence: 99%